2007
DOI: 10.2165/00019053-200725120-00007
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antiplatelet Therapy in Secondary Prevention of Cardiovascular Events

Abstract: The cost-effectiveness estimates presented in this article support the NICE guidelines for the use of antiplatelets for the prevention of cardiovascular events. Based on these pharmacoeconomic data alone, aspirin should be prescribed for primary or secondary prevention among patients at high risk of cardiovascular events, dipyridamole for the secondary prevention of stroke (for a maximum of 5 years), and clopidogrel for the treatment of symptomatic cardiovascular disease or acute coronary syndrome (for a maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The cost of treating subsequent ACS events (long term and transient) were calculated using the NHS reference costs [35] and the cost of follow up was obtained from Heeg et al [36]. The daily cost of rehabilitation from an ACS event was calculated from the NHS reference costs and the duration of rehabilitation was based on clinical opinion.…”
Section: Cost-effectiveness Evidencementioning
confidence: 99%
“…The cost of treating subsequent ACS events (long term and transient) were calculated using the NHS reference costs [35] and the cost of follow up was obtained from Heeg et al [36]. The daily cost of rehabilitation from an ACS event was calculated from the NHS reference costs and the duration of rehabilitation was based on clinical opinion.…”
Section: Cost-effectiveness Evidencementioning
confidence: 99%
“…63 Using data from both MI and stroke studies, they also concluded that the combination of ASA and ER dipyridamole for secondary stroke prevention was more cost-effective than ASA alone and, in indirect comparisons, than clopidogrel. 62 …”
Section: Economic Analyses Of Cost-effectiveness Of Antiplatelet Thermentioning
confidence: 99%
“…The cost of a non-vascular death is based on an assumption from another economic model 104 that estimated the cost of dying from unrelated causes to be approximately £250.…”
Section: Summary Of Costs and Resource Use Event Costsmentioning
confidence: 99%